A Global Comparison Between Brand-Name and Generic Drugs - Chawla, Karan; Tofighi, Taraneh; Agarwal, Arnav; Thomas, Jason; Mondal, Tapas (Indian Journal of Pharmacy Practice)
While the use of cheaper bioequivalent generic drugs over brand-name drugs has been widely discussed in literature, their market pricing and subsequent use is largely shaped by government policy-making as well as consumer and corporate decision-making. Analysis of literature shows that drug development and testing costs, degree of health care privatization, and pharmaceutical reimbursement all impact the profitability of brand-name drugs within and beyond their patent period. Furthermore, jurisdiction-specific government controls and policies influence the affordability and accessibility of both drug variants. This literature review focuses on: a) analyzing the policies and expenses associated with gaining approval for brand-name and generic drugs, and their subsequent influence on drug pricing; and b) comparing and contrasting government controls and policies between Canada, the United States, European nations, and developing countries.
Keywords: brand-name drugs; generic drugs; health policy; drug pricing; global comparison